Study of hypoglycemic effect of Fenugreek seed extracts - Bilal, Rand Ibrahim; Hasan, Nouma; Muhammad, Dima (Journal of medical and pharmaceutical sciences, 2022)
Trigonella foenum graecum (Fenugreek) is a popular herb widely used for culinary and pharmaceutical purposes. The seeds of the plant have been intensively studied, as they exhibit plenty of pharmacological properties. The objective of the current research was to investigate the hypoglycemic effect of fenugreek seeds in vitro and in vivo. Aqueous (Aq. ex) and ethyl acetate (ETAC. ex) extracts were prepared from the grinded seeds. The α-amylase inhibitory activity assay was used to evaluate the hypoglycemic effect in vitro. Acarbose (the standard drug) was used as a positive control. While the in vivo glucose tolerance test was assessed in normal and alloxan-induced diabetic mice. Glimepiride was used as a standard drug. Different concentrations from both extracts were used to evaluate the hypoglycemic effect both in vitro and in vivo. The in vitro results suggested that the ETAC. ex had significantly (P< 0.05) higher α-amylase inhibitory activity with IC50 of 106.39 µg/ml than the Aq. ex with IC50 = 159.55 µg/ml. However, it remained below the inhibitory activity of acarbose (IC50 = 68.92 µg/ml) dose-dependent. In vivo, the oral administration of ETAC. ex in alloxan-induced diabetic mice significantly decreased the rise of blood glucose levels (p< 0.05) after 30, 60, and 90 min of glucose administration compared to the diabetic mice which did not receive any treatment and sometimes similarly to diabetic mice which were treated with Glimepiride. Thus, this study concludes that fenugreek may have hypoglycemic activity, being able to moderately inhibit the intestinal absorption of glucose and possibly by other mechanisms.
Keywords: Trigonella foenum graecum; anti-diabetic effect; α- amylase IC50; Alloxan; diabetic mice